The construction of a hypoxia-based signature identified CA12 as a risk gene affecting uveal melanoma cell malignant phenotypes and immune checkpoint expression - Yin, Yan; Du, Wei; Li, Fei (Frontiers in Oncology, 2022)
Abstract Uveal melanoma (UM) is a deadly intraocular neoplasm in the adult population and harbored limited therapeutic effects from current treatment. Here, we aimed to investigate the role of hypoxia in UM progress. We adopted TCGA (the Cancer Genome Atlas) dataset as a training cohort and GEO (Gene Expression Omnibus) datasets as validating cohorts. We first used consensus clustering to identify hypoxia-related subtypes, and the C1 subtype predicted an unfavorable prognosis, exhibited high infiltration of immunocytes and globally elevated immune checkpoint expression. Besides, the patients with the C1 subtype were predicted to respond to the PD-1 treatment. By the LASSO (Least absolute shrinkage and selection operator) algorithm, we constructed a hypoxia risk score based on the hypoxia genes and identified 10 genes. The risk score predicted patient survival with high performance and the high-risk group also harbored high immunocyte infiltration and immune checkpoint expression. Further, we confirmed that the risk genes were upregulated under hypoxia, and knockdown of CA12 inhibited the EMT (epithelial-mesenchymal transition) process, clone formation ability, and the G1/S phase transformation of the UM cells. The CD276 was also downregulated when CA12 knockdown was performed. These results validated the prognostic role of hypoxia signature in UM and demonstrated that CA12 was a critical factor for UM cell progression as well as a target to improve immunotherapeutic effects. We believe our study contributed to the understanding of hypoxia’s roles in UM and provided a novel target that will benefit future therapeutic strategies development.